Pengaruh Motivasi, Gaya Kepemimpinan, Fasilitas Kerja, Dan Kompensasi Terhadap Kepuasan Kerja Karyawan (Studi Kasus Pada Multi-Mart 41 Batanghari) - Diputra, Andi Ahmad Cahya; Suryadi, Suryadi (Universitas Muhammadiyah Metro, 2022)
Andi Ahmad Cahya Diputra, 2021. The Effect of Motivation, Leadership Style, Work Facilities, and Compensation on Employee Job Satisfaction (Case Study at Multi-Mart 41 Batanghari). Undergraduate Thesis of Management Study Program, Faculty of Economics and Business, Universitas Muhammadiyah Metro. Supervisor (1) Dr. H. Febriyanto, S.E., M.M. (2) H. Suryadi, S.E., M.M. The purpose of this study was to determine the effect of motivation, leadership style, work facilities, and compensation on employee job satisfaction at Multi-Mart 41 Batanghari. This study uses quantitative research methods with questionnaires in the form of written questions given to respondents related to motivation, leadership style, work facilities, and compensation for employee job satisfaction. The sampling technique used is Non Probability Sampling with a saturated sample (census). Data analysis techniques used by researchers are validity test, reliability test, normality test, linearity test, homogeneity test and hypothesis testing in the form of multiple linear regression analysis, t-est, f-test, r2 test (Coefficient of determination) with data processing using SPSS version. 20. The results showed that simultaneously motivation, leadership style, work facilities, and compensation had a positive and significant effect on employee job satisfaction. Partially, motivation has a positive and significant effect on employee job satisfaction, leadership style has a positive and significant effect on employee job satisfaction, work facilities have a positive and significant effect on employee job satisfaction, and compensation has no and no significant effect on employee job satisfaction. Keywords: Motivation, Leadership Style, Work Facilities, Compensation, Job Satisfaction